ANALISIS SUSEPTIBILITAS MAGNETIK TANAH LAPISAN ATAS SEBAGAI INDIKATOR BENCANA LONGSOR DI BUKIT SULA KECAMATAN TALAWI KOTA SAWAHLUNTO - Arif Budiman; Dwi Puryanti; Febri Naldi (Universitas Riau, 2018)
Landslide is a disaster that can harm properties and souls. Losses due to landslide can be minimized if there are known signs of landslide.. In this research, the landslide indicator is known through the analysis of the magnetic susceptibility of topsoil. This research is a case study conducted at Bukit Sula, Talawi District, Sawahlunto City.Soil samples were taken from two locations in Sula Hill, which are vegetated location (location A) and unvegetated location (location B). This research’s samples took with downward vertical of each 100 m was taken with a space range of 5 m, so that is obtained 21 sampling points at each of these locations. Measurement of magnetic susceptibility value using Bartington Magnetic Susceptibility Meter measured at two frequencies, namely low frequency of 0.465 kHz (χLF) and high frequency of 4.65 kHz (χHF). At location A the obtained average value of χLF is 804.05×10-8 m3kg-1while the average value of χHF is 804.25×10-8 m3kg-1. At location B the obtained average value of χLF is 9.85×10-8 m3kg-1, while the average value of χHF is 9.64×10-8 m3kg-1. XRF test result showed that magnetic minerals in samples at both locations a hematit (Fe2O3). Based on the comparison of susceptibility value and concentration of hematite and quartz minerals between sample of location A and location B, it can be said that location B has been eroded. Based on the presence of superparamagnetic grain, the samples taken from location B have finer grains than the samples at location A. Scanning Electron Microscope (SEM) also shows that sample B has finer grains than the sample B. These are because location B is an area without vegetation, causing rain drop directly into the soil and can decrease the level of soil grain attachment. Therefore, location B more likely occurred landslide than location A.